2018
DOI: 10.1177/0363546518816690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultra-Purified Alginate Gel Implantation on Meniscal Defects in Rabbits

Abstract: Background: Many tissue-engineered methods for meniscal repair have been studied, but their utility remains unclear. Hypothesis: Implantation of low-endotoxin, ultra-purified alginate (UPAL) gel without cells could induce fibrocartilage regeneration on meniscal defects in rabbits. Study Design: Controlled laboratory study. Methods: Forty-two mature Japanese White rabbits were divided into 2 groups of 21 animals each. In each animal, a cylindrical defect measuring 2 mm in diameter was created with a biopsy punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
(57 reference statements)
1
18
0
Order By: Relevance
“… 13 Initial studies of implantation of this alginate reported no infections or allergic reactions in rabbit and canine models. 19 , 40 The low endotoxin level enables safe clinical application of the UPAL gel because it does not induce immunologic reactions to the implanted material. 11 , 14 The current clinical and radiographic findings suggested that no infections or allergic reactions occurred in any of the 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Initial studies of implantation of this alginate reported no infections or allergic reactions in rabbit and canine models. 19 , 40 The low endotoxin level enables safe clinical application of the UPAL gel because it does not induce immunologic reactions to the implanted material. 11 , 14 The current clinical and radiographic findings suggested that no infections or allergic reactions occurred in any of the 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate, obtained from brown algae, is an anionic polysaccharide that exhibits remarkably good scaffold-forming properties and is biocompatible, inexpensive and abundant ( Lee and Mooney, 2012 ). Furthermore, alginate hydrogels can be crosslinked by various materials (e.g., Ca 2+ ) for bioactive agents and cell delivery ( Lee and Mooney, 2012 ; Venkatesan et al, 2015 ; Kim et al, 2019 ). By combining collagen, alginate (A) and oxidized alginate (ADA), Gupta’s group designed self-healing interpenetrating network (IPN) hydrogel-loaded scaffolds with dual crosslinking [Ca 2+ -based ionic crosslinking and Schiff base reaction crosslinking (A-A, A-ADA)] capabilities, which revealed great potential for supporting fibrochondrocyte behavior and chondrogenesis in vitro ( Gupta et al, 2020a ).…”
Section: Polymers For Meniscal Tissue Engineering Applicationsmentioning
confidence: 99%
“…77,78 Alginate hydrogels can be easily crosslinked by various materials (e.g., Ca 2+ ) for bioactive agent and cell delivery. 61,62,79 At different molar ratios, chitosan was successfully crosslinked with polyvinyl alcohol using urethane prepolymer chains. 80 Another strategy is to use combinational approaches.…”
Section: Natural Polymersmentioning
confidence: 99%
“…The reparative tissue in the UPAL gel group exhibited superior stiffness (27.8 -6.2 N/mm) after 12 weeks. 62 In addition to their role as conventional tissue engineering constructs, as DDSs, natural polymers can be easily fabricated as hydrogels, microcarriers, 3D scaffolds, and fibers. For example, considering the necessity of the chondrogenesis of stem cells in meniscal repair and regeneration, Deng et al 87 incorporated HA into poly-D,L-lactic acid/polyethylene glycol/poly-D,L-lactic acid (PDLLA-PEG) hydrogel and then loaded it with TGF-b3 and human bone marrow-derived mesenchymal stem cells (BM-MSCs).…”
Section: Natural Polymersmentioning
confidence: 99%